The Combination of Tamarindus indica and Coenzyme Q10 can be a Potential Therapy Preference to Attenuate Cadmium-Induced Hepatorenal Injury - Amany Abdelnaby; Nabila Abdel-Aleem; Ayman Mansour; Afaf Abdelkader; Afaf Abdelkader; Amany N. Ibrahim; Safwa M. Sorour; Enas Elgendy; Heba Bayoumi; Shaymaa M. Abdelrahman; Samah F. Ibrahim; Ilhaam Alsaati; et al. (Frontiers Media S.A., 2022)
Cadmium (Cd) is a hazardous environmental pollutant that menaces human and animal health and induces serious adverse effects in various organs, particularly the liver and kidneys. Thus, the current study was designed to look into the possible mechanisms behind the ameliorative activities of Tamarindus indica (TM) and coenzyme Q10 (CoQ) combined therapy toward Cd-inflicted tissue injury. Male Wistar rats were categorized into seven groups: Control (received saline only); TM (50 mg/kg); CoQ (40 mg/kg); Cd (2 mg/kg); (Cd + TM); (Cd + CoQ); and (Cd + TM + CoQ). All the treatments were employed once daily via oral gavage for 28 consecutive days. The results revealed that Cd exposure considerably induced liver and kidney damage, evidenced by enhancement of liver and kidney function tests. In addition, Cd intoxication could provoke oxidative stress evidenced by markedly decreased glutathione (GSH) content and catalase (CAT) activity alongside a substantial increase in malondialdehyde (MDA) concentrations in the hepatic and renal tissues. Besides, disrupted protein and lipid metabolism were noticed. Unambiguously, TM or CoQ supplementation alleviated Cd-induced hepatorenal damage, which is most likely attributed to their antioxidant and anti-inflammatory contents. Interestingly, when TM and CoQ were given in combination, a better restoration of Cd-induced liver and kidney damage was noticed than was during their individual treatments.